Multi-Locus Genome-Wide Association Study of Four Yield-Related Traits in Chinese Wheat Landraces - Lin, Yu; Zhou, Kunyu; Hu, Haiyan; Jiang, Xiaojun; Yu, Shifan; Wang, Qing; Li, Caixia; Ma, Jian; Chen, Guangdeng; Yang, Zisong; Liu, Yaxi (Frontiers in Plant Science, 2021)
Wheat (Triticum aestivum L.) is one of the most important crops in the world. Here, four yield-related traits, namely, spike length, spikelets number, tillers number, and thousand-kernel weight, were evaluated in 272 Chinese wheat landraces in multiple environments. Five multi-locus genome-wide association studies (FASTmrEMMA, ISIS EN-BLASSO, mrMLM, pKWmEB, and pLARmEB) were performed using 172,711 single nucleotide polymorphisms to identify yield-related quantitative trait loci (QTL). A total of 27 stable QTL were identified by more than three models. Nine of these QTL (QSl.sicau-1A, QSl.sicau-2A, QSl.sicau-2B, QSn.sicua-2A.1, QSn.sicau-2A.3, QSn.sicua-5A, QSn.sicau-7A, QTn.sicua-6D, and QTkw.sicau-3A) were consistent with those in previous studies. The remaining 18 QTL may be novel. We identified a major QTL, QTkw.sicau-4B, with up to 18.78% of phenotypic variation explained. The developed kompetitive allele specific polymerase chain reaction marker for QTkw.sicau-4B was validated in two recombinant inbred line populations with an average phenotypic difference of 16.07%. After combined homologous function annotation and expression analysis, TraesCS4B01G272300 was the most likely candidate gene for QTkw.sicau-4B. Our findings provide new insights into the genetic basis of yield-related traits and offer valuable QTL to breed wheat cultivars via marker-assisted selection.